Does the antimicrobial-impregnated peripherally inserted central catheter decrease the CLABSI rate in neonates? Results from a retrospective cohort study - Bayoumi, Mohammad A. A.; van Rens, Matheus F. P. T.; Chandra, Prem; Masry, Alaa; D’Souza, Sunitha; Khalil, Amr M.; Shadad, Afaf; Alsayigh, Safaa; Masri, Razan M.; Shyam, Sunitha; Alobaidan, Fatima; Elmalik, Einas E. (Frontiers in Pediatrics, 2022)
Background The use of antimicrobial-impregnated peripherally inserted central catheters (PICCs) has been introduced in the last few years to neonatal units aiming to reduce central line-associated bloodstream infection (CLABSI). Methods This retrospective observational study aimed to compare the CLABSI rates and other catheter-related parameters including the insertion success rates and catheter-related complications in the antimicrobial-impregnated and conventional (ordinary) PICCs in NICU between 2017 and 2020. Results Our dedicated PICC team including physicians and nurses inserted 1,242 conventional (PremiCath and NutriLine) and 791 antimicrobial-impregnated PICCs (PremiStar) over the study period from 2017 to 2020. Of those 1,242 conventional PICCs, 1,171 (94.3%) were 1 Fr single lumen and only 71 (5.7%) were 2 Fr double lumen. The mean ± SD [median (IQR)] for the birth weight in all babies who had a PICC line was 1,343.3 ± 686.75 [1,200 (900, 1,500)] g, while the mean ± SD for the gestational age was 29.6 ± 4.03 [29 (27, 31)] weeks. The mean ± SD [median (IQR)] age at the time of insertion for all catheters was 9.3 ± 21.47 [2 (1, 9)] days, while the mean ± SD [median (IQR)] dwell time was 15.7 ± 14.03 [12 (8, 17)] days. The overall success rate of the PICC insertion is 1,815/2,033 (89.3%), while the first attempt success rate is 1,290/2,033 (63.5%). The mean ± SD [median (IQR)] gestational age, birth weight, age at catheter insertion, and catheter dwell time were 28.8 ± 3.24 [29, (26, 31)] weeks, 1,192.1 ± 410.3 [1,150, (900, 1,450)] g, 6.3 ± 10.85 [2, (1, 8)] days, and 17.73 ± 17.532 [13, (9, 18)] days in the antimicrobial-impregnated catheter compared with 30.1 ± 4.39 [29, (27, 32)] weeks (P < 0.001), 1,439.5 ± 800.8 [1,240, (920, 1,520)] g (P < 0.001), 11.1 ± 25.9 [1, (1, 9)] days (P < 0.001), and 14.30 ± 10.964 [12, (8, 17)] days (P < 0.001), respectively, in the conventional PICCs. The use of the antimicrobial-impregnated catheter was not associated with any significant reduction in the CLABSI rate (per 1,000 days dwell time), either the overall [P = 0.11, risk ratio (RR) (95% CI): 0.60 (0.32, 1.13)] or the yearly CLABSI rates. Conclusions The use of miconazole and rifampicin-impregnated PICCs did not reduce the CLABSI rate in neonates compared with conventional PICCs. However, it has a higher overall rate of elective removal after completion of therapy and less extravasation/infiltration, occlusion, and phlebitis compared with the conventional PICCs. Further large RCTs are recommended to enrich the current paucity of evidence and to reduce the risk of bias. Neonatal PICCs impregnation by other antimicrobials is a recommendation for vascular access device manufacturers.